(untitled) (Journal of Philosophy Culture and Political Science, 2025)
The current stage of human growth, which is marked by instability, contradictions, and the nonlinearity of global processes, is examined in this article. The universalist concept of globalization, including its cultural component, is in crisis due to the development of information and communication technologies, the escalation of tensions between rich and developing nations, and the growth of social and geopolitical conflicts. In light of this, the idea of cultural de-globalization has become more popular as a way to oppose unilateral cultural dominance and restore cultural subjectivity. The study’s goal is to pinpoint the key elements of cultural de-globalization and how it contributes to the evolution of the world order. In addition to discussing strategies for the resuscitation of regional identities, national languages, and symbolic systems, the study examines the historical development of the link between culture and civilization. The work’s scholarly innovation is its conception of de-globalization as a positive trend that fosters cultural heterogeneity. The findings’ relevance to the creation of cultural policies founded on communication, inclusion, and respect for the variety of civilizational models demonstrates the study’s practical significance. Key words: culture, civilization, globalization, de-globalization, slowbalization, cultural-historical types.